Effect of Spacing and Seedling Per Hill on the Performance of Aus Rice var. BRRI dhan48 (Bangladesh Agronomy Journal, 2018)
An experiment was conducted at the research field and laboratory in the Department of Crop Physiology and Ecology, Hajee Mohammad Danesh Science and Technology University, Dinajpur, during the period of April to August, 2016 to study the effect of spacing and number of seedlings hill-1 on the yield of Aus rice var. BRRI dhan48. Four spacing’s viz. 20 cm × 10 cm, 20 cm × 15cm, 20cm × 20 cm and 20 cm × 25cm and three number of seedlings hill-1 viz. 1, 2 and 4 were included in the study. Results indicated that the highest number of total tillers hill-1 (22.86), number of effective tillers hill-1 (21.24), number of grains panicle-1 (128.79) and 1000-grain weight (23.30g) were found with 20cm × 25cm spacing. The highest plant height (104.27 cm), number of leaves plant-1 (35.80), grain yield (3.06 tha-1), straw yield (3.37 tha-1) and harvest index were obtained from 20 cm × 10 cm spacing. The highest grain yield of 2.98 t ha-1 was obtained from 4 seedlings hill-1, while the lowest 2.47 t ha-1 from 1 seedlings hill-1. The highest grain yield of 3.40 tha-1 was obtained from 20 cm × 10 cm spacing with 4 seedlings hill-1 while the lowest grain yield of 2.21 tha-1 from the wider spacing. Results of the present study revealed that 20 cm x 10 cm spacing with 4 seedlings hill-1 combination was found to be the best for obtaining maximum grain yield of Aus rice var. BRRI dhan48.Bangladesh Agron. J. 2017, 20(2): 17-26